LEARNING MOTIVATION IN METACOGNITIVE MONITORING RELIABILITY - Kalamazh, Ruslana; Avhustiuk, Maria (Psychological Prospects Journal, 2018)
The paper tries to contribute to better understanding of the reliability of metacognitive monitoring. The research is centred in a precise theoretical framework of motivation in metacognitive monitoring of the learning activity of university students(n = 262; M = 19,5; SD = 1,87). Moreover, we aimed to study the role of the learning motivation in such metacognitive monitoring error as the illusion of knowing.To diagnose the role of the learning motivation in metacognitive monitoring reliability a method of motivation diagnosis by Ilyina (2003) was used provided by the study of the structure of motivation in the university activity. The results of the empirical study of the learning motivation in metacognitive monitoring are highlighted. In particular, the results show that among the most important characteristics, student motivation is aimed to provide better understanding of the nature of metacognitive monitoring reliability and can help in the annihilation of the negative impact of the illusion of knowing on metacognitive monitoring of the university learning activity. Those students who were focused on knowledge performed accurate metacognitive judgements. However, among the students targeted for occupation the accuracy of metacognitive monitoring was the highest (MaJOL = -.006; SD = .01; MaRCJ = -.006; SD = .02; MJOL = .03; SD = .02; MRCJ = .00; SD = .01) (p = .05). Possible prospectives of future investigations of the problem are also described.
Keywords: illusion of knowing, learning activity, metacognitive monitoring, motivation, reliability, self-regulated learning.